1980
DOI: 10.1172/jci109788
|View full text |Cite
|
Sign up to set email alerts
|

Captopril-induced Changes in Prostaglandin Production

Abstract: A B S T R A C T Captopril is a potent hypotensive agent whose efficacy has hitherto been attributed to its ability to alter either angiotensin II formation or kinin degradation. Our purpose was to examine captopril's acute effect on prostaglandin production, because changes in neither the renin-angiotensin nor the kallikrein-kinin systems appear adequate to account for the fall in arterial pressure. The plasma levels of' angiotensin II, kinins, and prostaglandins were determined in response to increasing doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(48 citation statements)
references
References 22 publications
3
45
0
Order By: Relevance
“…Cilazapril also increased the excretion of prostaglandin E2 metabolite which may reflect increased prostaglandin synthesis. An increase in prostaglandin E2 has been reported with captopril (Swartz et al, 1980;Moore et al, 1981) and enalapril (Oparil et al, 1983) and has been attributed to increased kinin levels (Swartz et al, 1980) or a direct effect of the drug on phospholipase activity (Swartz et al, 1980). Timw (min) Figure 8 Urinary water, sodium and potassium excretion following frusemide 20 mg intravenously in subjects pretreated with placebo (clear boxes) or cilazapril 5 mg (hatched boxes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cilazapril also increased the excretion of prostaglandin E2 metabolite which may reflect increased prostaglandin synthesis. An increase in prostaglandin E2 has been reported with captopril (Swartz et al, 1980;Moore et al, 1981) and enalapril (Oparil et al, 1983) and has been attributed to increased kinin levels (Swartz et al, 1980) or a direct effect of the drug on phospholipase activity (Swartz et al, 1980). Timw (min) Figure 8 Urinary water, sodium and potassium excretion following frusemide 20 mg intravenously in subjects pretreated with placebo (clear boxes) or cilazapril 5 mg (hatched boxes).…”
Section: Discussionmentioning
confidence: 99%
“…Captopril and enalapril cause acute natriuresis (Brunner et al, 1981;Hollenberg et al, 1981;McNabb et al, 1986;Navis et al, 1986) which may be accompanied by potassium retention (Atlas et al, 1979;Navis et al, 1986) or in the case of enalapril by kaliuresis (McNabb et al, 1985(McNabb et al, , 1986. Both drugs have been reported to increase prostaglandin levels (Swartz et al, 1980;Oparil et al, 1983) but there are no data for cilazapril.…”
Section: Introductionmentioning
confidence: 99%
“…However, synthesis of angiotensinogen by a tissue may cause a significant increase in the angiotensinogen concentration ofinterstitial fluid ofthat tissue. The concentration ofangiotensinogen in interstitial fluid is similar to that of plasma (78) (83). However, several studies have found no increase in plasma bradykinin levels in response to the orally active CEIs captopril and enalapril (84-86), although there is some question as to the accuracy of the methods used to measure plasma bradykinin levels (87).…”
mentioning
confidence: 99%
“…Many studies have shown less marked falls in plasma All (83)(84)(85)(86)98), but these results probably reflect methodological problems, including cross-reactivity by the elevated plasma levels of Al (99), and also a significant assay blank (98). The hypotensive effects of acute inhibition of All production may be due to inhibition of any of several All-dependent pressor mechanisms.…”
mentioning
confidence: 99%
“…The mechanisms by which Captopril suppresses inflammation are not known at the present time but it may be through the kinin-prostaglandin pathway. In this regard, Schwartz et al reported that the administration of Captopril to patients altered prostaglandin levels and suggested that these changes were associated with the hypotensive response (18).…”
Section: Resultsmentioning
confidence: 99%